Keanekaragaman Jenis Tumbuhan Bawah di Kawasan Hutan Dengan Tujuan Khusus Oelsonbai Kupang - Tri Putra Merden Fallo; Lusia Sulo Marimpan; Fadlan Pramatana (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
Forests are inhabited by various types of plants. These plants form a plant community that is closely interconnected with each other and the undergrowth is one of the components that form it. This research aims to examine the diversity of understory plants in forest areas with special purpose Oelsonbai Kupang. Data collection in this research was carried out using a purposive sampling method with a plot size of 2 x 2 m. Understory plant species diversity was calculated using the Shannon-Wienner diversity index. The results of the research show that there are 35 types of understory plants found in KHDTK Oelsonbai from 22 families, which are dominated by the Poaceae family. The diversity of understory plants is included in the medium category with a diversity index value of 2,81.